IT auditing using controls to protect information assets - Davis, Chris; Schiller, Mike; Wheeler, Kevin (McGraw-Hill, 2011)
Featuring real-world examples; ready-to-use checklists; and valuable templates; this guide explains; step by step; how to implement a successful; enterprise-wide IT audit program. --
Includes bibliographical references and index
Keywords: Computer networks -- Security measures; Computer security; Electronic data processing -- Auditing; Information audits; Réseaux d'ordinateurs; Sécurité; Mesures; Sécurité informatique; Information; Audit; COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; Computer networks; Security measures; Electronic data processing; Auditing